2010
DOI: 10.3201/eid1610.100399
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus and Increased Risk for Malaria Infection

Abstract: A case–control study of 1,466 urban adults in Ghana found that patients with type 2 diabetes mellitus had a 46% increased risk for infection with Plasmodium falciparum. Increase in diabetes mellitus prevalence may put more persons at risk for malaria infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
9
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 13 publications
1
82
9
3
Order By: Relevance
“…Previous studies have shown that carriage of the sickle cell trait confers increased susceptibility to P. ovale infection ( 20 ) and that diabetes and HIV infection confer increased susceptibility to P. falciparum infection ( 30 ). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that carriage of the sickle cell trait confers increased susceptibility to P. ovale infection ( 20 ) and that diabetes and HIV infection confer increased susceptibility to P. falciparum infection ( 30 ). …”
Section: Discussionmentioning
confidence: 99%
“…Based on our current results, we speculate that this mechanism may contribute to the bacterial and viral infection susceptibility seen in patients with type 2 diabetes. Clinical reports have demonstrated that type 2 diabetic patients have a high risk for infection (26)(27)(28). Recent reports have shown that type 2 insulin resistance is tightly linked with S6K1 activity via a negative feedback loop involving S6K1 that suppresses insulin signaling under conditions of nutrient overload (29).…”
Section: Discussionmentioning
confidence: 99%
“…Infection with malaria parasites can induce a rise in blood insulin levels above that of a normal healthy adult by as much as 10- to 35-fold [1, 2]. Given that the occurrence of type 2 diabetes is rising in malaria-endemic countries [3], compounded hyperinsulinemia in individuals affected by both diseases could become prevalent. In particular, a hallmark of type 2 diabetes is insulin resistance, which can often result in increased insulin secretion to compensate for the inability of the body to respond to insulin.…”
Section: Insulin and Insulin-like Growth Factor-1mentioning
confidence: 99%